Conditional Cooperation and Voluntary Contributions to Public Goods - Claudia Keser; Frans A.A.M. van Winden (Tinbergen Institute, 2000)
We compare a partners condition where the same small group of subjects plays arepeated public good game to astrangers condition where subjects play this game in changing group formations.Subjects in the partners conditioncontribute from the first period on significantly more to the public good thansubjects in the strangers condition. In thestrangers condition, contributions show a continual decay, while in the partnerscondition, contributions fluctuate on ahigh level until they decrease in the final periods. We interpret subjects'behavior in terms of conditional cooperationwhich is characterized by both future-oriented and reactive behavior.
Keywords: C92; H41; 330; Experimental Economics; Public Goods; Voluntary Contributions; Cooperation; Öffentliche Güter; Test; Fundraising; Theorie; Wiederholte Spiele